(untitled) (Journal of Madenat Alelem, 2010)
This research was conducted to survey the fungi located in the revere of Al – Hila city from November 2008 till April 2009. Four locations ( Jumaijuma, City center, Marana and Taliaa ) were selected represent the city center and different places from the Hila city. Results showed that there were 4 genera ( aquatic fungi ) belong to Oomyctes isolated from water of Hila revere and identified as : Achlya , Aphanomyces , Dictyuchus and Saprolegnia , in addition to 3 other genera belong to other groups isolated and identified as : Fusarium , Pythium and Rhizoctonia . City center regions ( 2 & 3 ) were recorded the highest level of fungi because of the high concentrations of nutrients and minerals came from the city to these regions. Some physical and chemical parameters of water were determined.